Opioid sparing effect of ketamine in military prehospital pain management—A retrospective study. (18th August 2022) - Cohen, Bar; Talmy, Tomer; Gelikas, Shaul; Radomislensky, Irina; Kontorovich-Chen, Diana; Cohen, Barak; Benov, Avi; Avital, Guy
Abstract : The use of low-dose ketamine in the pre-hospital military setting may provide an opioid-sparing effect while reduction in pain scores is not significantly different. Abstract : BACKGROUND: Opioids are the most commonly used analgesics in acute trauma, but are limited by slow onset and significant adverse effects. Ketamine is an effective and widely used analgesic. This study was aimed to evaluate the effectiveness and opioid-sparing effects of ketamine when used in prehospital military trauma setting. METHODS: A retrospective analysis of a prehospital military trauma registry between 2014 and 2020. Inclusion criteria were 16 years or older, two or more documented pain assessments, at least one indicating severe pain, and administration of opioids and/or low-dose ketamine. Joint hypothesis testing was used to compare casualties who received opioids only to those who received ketamine on outcomes of pain score reduction and opioid consumption. RESULTS: Overall, 382 casualties were included. Ninety-one (24%) received ketamine (21 as a single analgesic), with a mean dose of 29 mg (standard deviation, 11). Mean reduction in pain scores (on an 11-point scale) was not significantly different; 4.3-point (2.8) reduction in the ketamine group and 3.7 points (2.4) in the opioid-only group ( p = 0.095). Casualties in the ketamine group received a median of 10 mg (interquartile range, 3.5–25) of morphine equivalents (MEs) compared with a median of 20 ME (10, 20) in the opioid-only group. In a multivariable multinomial logistic regression, casualties in the ketamine group were significantly more likely to receive a low (1–10 ME) rather than a medium (11–20 ME) dose of opioids compared with the opioid-only group (odds ratio, 0.032; 95% confidence interval, 0.14–0.75). CONCLUSION: The use of ketamine in the prehospital military setting as part of a pain management protocol was associated with a low rather than medium dose of opioids in a multivariable analysis, while the mean reduction in pain scores was not significantly different between groups. Using ketamine as a first-line agent may further reduce opioid consumption with a similar analgesic effect. LEVEL OF EVIDENCE: Therapeutic/care management; Level IV. Abstract :